2021
DOI: 10.1177/09500170211024467
|View full text |Cite
|
Sign up to set email alerts
|

Trade Unions, Bargaining Coverage and Low Pay: A Multilevel Test of Institutional Effects on Low-Pay Risk in Germany

Abstract: Employment relations scholars argue that industrial relations institutions reduce low pay among the workforce, while the insider-outsider literature claims that unions contribute to increase the low-pay risk among non-union members. This article tests these expectations by distinguishing, respectively, between the individual effect of being a union member or covered by collective agreements and the sectoral effect of strong trade unions or encompassing collective agreements. Findings from multilevel logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Third, the temporality of the potential trade-offs between welfare state spending and environmental policies is not fully resolved. Fourth, trade union organizations and wage bargaining institutions could also in principle help address the insecurity of certain workers’ groups (see Benassi and Vlandas, 2015 and 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the temporality of the potential trade-offs between welfare state spending and environmental policies is not fully resolved. Fourth, trade union organizations and wage bargaining institutions could also in principle help address the insecurity of certain workers’ groups (see Benassi and Vlandas, 2015 and 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, high collective bargaining coverage ensures more equal wages within sectors through sectoral bargaining. Conversely, research has shown that decreasing collective bargaining coverage is associated with higher levels of low-paid jobs (Benassi and Vlandas, 2021). Last but not least, high union density is likely to be a proxy for worker power in society and politics, enabling them to push for more redistributive politics (Bengtsson, 2014; Pontusson, 2013).…”
Section: The Epi and Income Inequalitymentioning
confidence: 99%
“…Union density is positively associated with a higher probability of fixed-term employees transitioning either to permanent contracts or to unemployment (Fervers and Schwander, 2014). In Germany, non-unionized workers are more likely to experience low pay in highly unionized sectors, while high bargaining coverage at the sectoral level decreases the risk of low pay for everyone, even those who are not covered by collective bargaining agreements (Benassi and Vlandas, 2021); this is because the absence of a strong tripartite collective bargaining agreement leaves labour weaker in some parts of the economy (Thelen, 2012).…”
Section: Collective Bargaining Anti-dualization Policies and Better H...mentioning
confidence: 99%